A functional biomechanical analysis of an elite cyclist - Saju, J.; Ganason, R.; Ahmad Pharmy Jalil; Zulkarnain Shazrain Aizam; Wilson, B. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
We are investigating possible causes of chronic back pain of an otherwise healthy elite cyclist while cycling. Asymmetry in the lower limbs and patterns of pelvic, hip, knee and ankle joint motion in gait and sports specific cycling movements were assessed.